Developing and launching the INNOPENA Internet platform to unblock the flow of innovative solutions between R&D and industry in Poland = Opracowanie i uruchomienie platformy INNOPENA dla usprawnienia przepływu innowacji pomiędzy sektorem B&R a przemysłem w Polsce - Zalewski, Romuald I.; Skawińska, Eulalia (Zielona Góra: Faculty of Economics and Management Press)
This paper presents actual, unsatisfactory innovative activity of processing industry in Poland and one of its regions named Wielkopolska (Greater Poland). The analysis uses data from international and internal sources, as well as results of special research programmes. Various barriers were identified and particularly very low level of cooperation between enterprises and R&D sector represented by universities, institutes of Polish Academy of Science and others. The aim of this paper is to present newly established Internet platform INNOPENA, which was built relying on the "open innovation" concept. There is a hope, that this new instrument will improve cooperation for better innovation activity, especially in favour of small and medium enterprises.
Keywords: Innovation; Open innovation; Innovative platform; INNOPENA; Innowacje; Innowacje otwarte; Platforma innowacyjna